Pelibatan Audiens Generasi Milenial Pada Program “Netizen Bertanya Ustad Menjawab”Di Televisi Muhammadiyah - Nabila Putri Falaqiah; Makroen Sanjaya (STIKes Ibnu Sina Ajibarang, 2024)
Audiences are the main consideration in the production of a TV program, and play a major role in determining the script that will be made. The